Metabolic Syndrome among Indigenous People (Orang Asli) in Peninsular Malaysia: A Systematic Review - Muslimah Ithnin; Nadia Mohd Effendy; Mohd Dzulkhairi Bin Mohd Rani; Khairun Nain Nor Aripin; Norsham Juliana Nordin; Nadeeya'ayn Umaisara Mohamad Nor (Akademi Sains Malaysia, 2024)
Indexed by Scopus